Do size, shape, and alignment parameters of the femoral condyle affect the trochlear groove tracking? A morphometric study based on 3D- computed tomography models in Chinese people - Du, Zhe; Chen, Shichang; Yan, Mengning; Yue, Bing; Zeng, Yiming; Wang, You (BMC musculoskeletal disorders, 2017)
Background Our study aimed to investigate whether geometrical features (size, shape, or alignment parameters) of the femoral condyle affect the morphology of the trochlear groove. Methods Computed tomography models of 195 femurs (97 and 98 knees from male and female subjects, respectively) were reconstructed into three-dimensional models and categorised into four types of trochlear groove morphology based on the position of the turning point in relation to the mechanical axis (types 45°, 60°, 75°, and 90°). Only subjects with healthy knees were included, whereas individuals with previous knee trauma or knee pain, soft tissue injury, osteoarthritis, or other chronic diseases of the musculoskeletal system were excluded. The size parameters were: radius of the best-fit cylinder, anteroposterior dimension of the lateral condyles (AP), and distal mediolateral dimension (ML). The shape parameters were: aspect ratio (AP/ML), arc angle, and proximal- and distal- end angles. The alignment parameters were: knee valgus physiologic angle (KVPA), mechanical medial distal femoral angle (mMDFA), and hip-knee-ankle angle (HKA). All variables were measured in the femoral condyle models, and the means for each groove type were compared using one-way analysis of variance. Results No significant difference among groove types was observed regarding size parameters. There were significant differences when comparing type 45° with types 60°, 75°, and 90° regarding aspect ratio and distal-end angle ( p < 0.05), but not regarding proximal-end angle. There were significant differences when comparing type 90° with types 45°, 60°, and 75° regarding KVPA, mMDFA, and HKA ( p < 0.05). Conclusion Among size, shape, and alignment parameters, the latter two exhibited partial influence on the morphology of the trochlear groove. Shape parameters affected the trochlear groove for trochlear type 45°, for which the femoral condyle was relatively flat, whereas alignment parameters affected the trochlear groove for trochlear type 90°, showing that knees in type 90° tend to be valgus. The morphometric analysis based on trochlear groove classification may be helpful for the future design of individualized prostheses.